Parasitic behaviour of Telenomus sp. on Spodoptera frugiperda - ROJAS-ALVAREZ, LILIANA; GARCÍA-ROA, FULVIA (Revista Colombiana de Entomología, 1995)
The egg parasite Telenomus sp. (Hymenoptera: Scelionidae) could be an important biological alternative to be used in the diversification of biological control programs. Laboratory and field studies are being carried out by Corpoica at the Palmira Research Center (T=25°C; R.H.=65%) to broaden the 'knowledge on the behavior of this parasitoid that allows a mass-rearing production and a successful liberation in Spodoptera frugiperda (J.E. Smith) infested fields. The results show that Telenomus emerge at different times depending on the sex: 10 to 11 days for males and 13 to 14 days for females. The maximum longevity of Telenomus sp. in the laboratory was 20-22 days, and the optimum time of exposition of the host to the parasitoid was 24 hours, and the best parasitism was obtained on eggs with less than 24 hours of incubation. The parasitism registered in the laboratory was above 90%.